2018
DOI: 10.1002/pbc.27426
|View full text |Cite
|
Sign up to set email alerts
|

Increased clinical trial enrollment among adolescent and young adult cancer patients between 2006 and 2012–2013 in the United States

Abstract: Although disparities in enrollment onto clinical trials remain for AYAs with cancer, our study identified increasing overall clinical trial participation over time. Further, we identify promising trends in enrollment uptake among AYAs 25-29 years of age and the uninsured.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 23 publications
(77 reference statements)
1
48
1
Order By: Relevance
“…They also found promising trends in patients aged 25 to 29 years, who doubled their enrollment from 6.3% in 2006 to 13.2% in 2012 and 2013. In addition, the authors noted a decrease in uninsured patients and improved trial enrollment among those who were uninsured, from 5.7% in 2006 to 12.8% in 2012 and 2013 …”
Section: Improving Outcomes Of Ayas With Cancermentioning
confidence: 96%
“…They also found promising trends in patients aged 25 to 29 years, who doubled their enrollment from 6.3% in 2006 to 13.2% in 2012 and 2013. In addition, the authors noted a decrease in uninsured patients and improved trial enrollment among those who were uninsured, from 5.7% in 2006 to 12.8% in 2012 and 2013 …”
Section: Improving Outcomes Of Ayas With Cancermentioning
confidence: 96%
“…The lack of enrollment of specific patient populations in CCTs prevents the determination of optimal treatment regimens and the collection of essential biospecimens needed to target the underlying disease biology in future studies. AYA enrollment in CCTs has significantly lagged behind the enrollment of pediatric patients . Enrollment is estimated to range between 3% and 14% for all AYAs, but enrollment rates vary within the AYA population .…”
Section: Introductionmentioning
confidence: 99%
“…AYA enrollment in CCTs has significantly lagged behind the enrollment of pediatric patients . Enrollment is estimated to range between 3% and 14% for all AYAs, but enrollment rates vary within the AYA population . Previous research has consistently found higher enrollment rates in adolescent patients than patients in their 20s and 30s …”
Section: Introductionmentioning
confidence: 99%
“…In addition, hematopoietic stem cell transplantation (HSCT) is less used in pediatric trials . Other factors contributing to the differences between the two types of trials relate to the greater experience observed in pediatric centers and higher adherence of AYA treated in pediatric vs adult cancer centers in some countries . However, a recently published study by three adult US cooperative groups (CALGB, ECOG, and SWOG) demonstrated that the use of a full pediatric regimen for young adults (YA) with ALL up to the age of 40 years was feasible and effective, resulting in improved survival rates compared to historical controls …”
Section: Introductionmentioning
confidence: 99%